DSAP-WeedNet: A Down-Scale Attention-Guided Lightweight Network for Real-Time Weed Detection Enabling Precision Control in Potato Fields - Lei Han; Yi-Teng Wu; Ke-Jun Fan; Rui-Feng Wang; Wen-Hao Su (Potato Research, 2026)

Vegetation conversion and microtopography jointly regulate soil microbial necromass in floodplain wetlands - Xiaomin Zhang; Yakov Kuzyakov; Rui Su; Siwen Hu; Qinglong L. Wu; Dayong Zhao; Jin Zeng (CATENA, 2026)

Structurally diverse sesquiterpenoids from Curcuma longa and their anti-inflammatory activities - Guang-Han Li; Chun-Mei Qiu; Guang-Xu Wu; Miao Dai; Rui Feng; Hai-Guo Su; Liang Xiong (Phytochemistry, 2026)

Melatonin alleviates chilling injury in postharvest banana fruit by modulating membrane lipid and phenolic metabolism - Jing Lin; Rui Zhang; Qi Chen; Weiqi Liang; Yanting Wu; Wenbing Su; Wei Wei; Hetong Lin; Zhongqi Fan (Postharvest Biology and Technology, 2026)

Trade-off mechanisms between N2O emissions and nitrogen multifunctionality in a lake littoral mesocosm wetland under seasonal water-level fluctuations: insights from metagenomics and machine learning - Rui Su; Dayong Zhao; Xiaomin Zhang; Qinglong L. Wu; Jin Zeng (Water Research, 2026)

Characteristics and source analysis of fluorescent aerosol particles at a typical rural site in the North China Plain during autumn and winter - Yang Zhou; Wei Hu; Siyao Yue; Wanyun Xu; Rui Jin; Boran Hua; Zihe Li; Libin Wu; Junjun Deng; Jiangchuan Tao; Nan Ma; Hang Su; et al. (Atmospheric Environment, 2026)

Pseudofrenelopsis (Cheirolepidiaceae) from the Lower Cretaceous of northwestern China and its paleoclimatic and biogeographic significances - Rui-Qi Lou; Yi-Fan Liang; Bo-Jin Gou; Wan-Yu Huang; Jing-Yu Wu; Su-Ting Ding (Cretaceous Research, 2026)

An Attention-Enhanced Temporal Convolutional Network for Surrounding Rock Deformation Prediction in Mountain Tunnels - Rui Su; Yitao Yang; Guowen Xu; Ziqian Yang; Jie Yu; Ruohui Wang; Dong Zhou; Zhuolin Wu (Rock Mechanics and Rock Engineering, 2026)

Recycling aluminum-rich drinking water treatment sludge into ceramic membranes: Fabrication process and environmental impact assessment - Pu Li; Kunbo Wu; Wenhao Su; Zhiming Chen; Guofen Rui; Mingguo Peng; Jie Teng (Process Safety and Environmental Protection, 2026)

Reconstruction of atmospheric CO2 concentration changes during the Aalenian (Middle Jurassic) based on fossil cuticles of Ginkgoites and Czekanowskia from northwestern China - Yu Jiang; Rui-Qi Lou; Yi-Fan Liang; Bo-Jin Gou; Wan-Yu Huang; Jing-Yu Wu; Su-Ting Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A COF-spaced Plasmon-enhanced fluorescent nanocomposite for ultrasensitive and on-site dual-modality lateral flow immunoassay - Han Han; Junhua Su; Zhenzhen Liu; Zijin Tong; Lei Wu; Shihui Zhu; Wentao Zhao; Baohua Zhao; Rui Xiao (Chemical Engineering Journal, 2026)

Selection of targets for cancer mRNA vaccines: from laboratory to clinical application - Huacong Lu; Rui Wu; Xiaodong Su; Fusheng Liu; Sisi Liu; Junwen Zhang (Science China Life Sciences, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Ecosystem-specific composition and drivers of plastisphere resistome in freshwater and marine environments - Jianhong Shi; Chaoli Sun; Yinglong Su; Yifan Wu; Min Zhan; Chengyuan Ji; Rui Wang; Baoyi Lv (Environmental Research, 2026)

Seasonal variation and source apportionment of brown carbon light absorption in Tianjin, China: Insights from online monitoring and PMF modeling - Rui Qiao; Kaishe Su; Jingwen Zhang; Bolong Wang; Ziwei Zhan; Jinqiu Zhang; Jianhui Wu (Air Quality, Atmosphere & Health, 2026)

Iron-doped biocarriers enhanced nitrogen removal from saline wastewater in an unplanted constructed wetland-microbial electrolytic cell system - Longqiang Yi; Changyuan Liu; Xinyu Rong; Kexin Li; Ruina Zhang; Xin Su; Xinting Mu; Li Wan; Yinghai Wu; Rui Han (Journal of Environmental Management, 2025)

Dual-functional 3D-printed polyetheretherketone scaffolds with immunomodulatory nano‑calcium silicate/interleukin-4 coating synergistically enhance osteogenesis through macrophage M2 polarization and NF-κB pathway suppression - Xiaoyu Guo; Yanwen Su; Zixuan Wu; Zidong Wu; Kaili Liu; Junyu Yue; Yuning Qu; Kunzheng Wang; Jiankang He; Rui Ma; Pei Yang (Chemical Engineering Journal, 2025)

Improved nitrogen removal from real mariculture effluent by halotolerant bacterial consortium SND223: Preparation, entrapping application, and mechanism - Xin Su; Shihan Wang; Xiaoqian Cheng; Jing Song; Qing Li; Guixi Yao; Rui Han; Yinghai Wu (Bioresource Technology, 2025)

Deep learning approach for internal tide prediction based on China Ocean Reanalysis data - Rui Su; Jun Zhao; Senliang Bao; Hongli Fu; Huizan Wang; Xiaojiang Zhang; Xiang Wang; Can Ma; Weimin Zhang; Xinrong Wu (Ocean Engineering, 2025)

Vitamin E alleviates ammonia‑nitrogen and hypoxia co-exposure-induced intestinal damage in grass carp (Ctenopharyngodon idella) by modulating mitochondrial function, cellular autophagy and apoptosis - Rui Su; Ke Yao; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Hong-Mei Ren; Xiao-Wan Jin; Pei Wu (Aquaculture, 2025)

Upcycling of cathode materials from spent lithium-ion batteries cathode materials enabled by deep eutectic solvent - Yanshun Liao; Xianglei Meng; Hongwei Wu; Guang Yang; Xinyao Zhang; Rui Tang; Yali Li; Ni Yang; Yibiao Guan; Yuefeng Su; Feng Wu; Qing Huang (Journal of Environmental Chemical Engineering, 2025)

Directed evolution of Escherichia coli Nissle 1917 functioning as a methylotrophic chassis - Li-Hua Liu; Zhiqian Zhang; Bo Xu; Gangzhu Yang; Hua Cui; Lijun Su; Yu Zhang; Baoqing Sun; Yi-Rui Wu; Ao Jiang (Chemical Engineering Journal, 2025)

Antifungal activity evaluation of three traditional Chinese herbs against biodeterioration of cultural heritage - Tianxiao Li; Huabing Zhang; Xiang Tan; Rui Zhang; Fasi Wu; Zongren Yu; Bomin Su (International Biodeterioration & Biodegradation, 2025)

Superficial Mycoses: A Mapping Through Bibliometric Research - Jintong Wu; Zijie Tang; Su Wang; Yuxin Qiu; Xinyu Nie; Chengxin Li; Rui Wang (Mycopathologia, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Dissimilatory nitrate reduction pathways drive high nitrous oxide emissions and nitrogen retention under the flash drought in the largest freshwater lake in China - Rui Su; Dayong Zhao; Xiaomin Zhang; Hongjie Zhang; Junxiang Cheng; Ligang Xu; Qinglong L. Wu; Jin Zeng (Water Research, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Late Neogene monsoonal climate in the southeastern margin of the Tibetan Plateau revealed by leaf physiognomy evidence - Zhuo-Er Wang; Gui-Hua Chen; Rui Cao; Zhi-Hui Song; Zhao-Shuai Wang; Huai Wang; Su-Ting Ding; Jing-Yu Wu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

Improved nitrate removal by polyvinyl alcohol/sodium alginate hydrogel beads entrapping salt-tolerant composite bioagent AHM M3 - Rui Han; Hongjing Ma; Xin Su; Jing Song; Peiwu Liu; Yinghai Wu; Ying Liu (Desalination, 2024)

TP53 to mediate immune escape in tumor microenvironment: an overview of the research progress - Kai-li Zhu; Fei Su; Jing-ru Yang; Ruo-wen Xiao; Rui-yue Wu; Meng-yue Cao; Xiao-ling Ling; Tao Zhang (Molecular Biology Reports, 2024)
Increasing evidence suggests that key cancer-causing driver genes continue to exert a sustained influence on the tumor microenvironment (TME), highlighting the importance of immunotherapeutic targeting of gene mutations in governing tumor progression. TP53 is a prominent tumor suppressor that encodes the p53 protein, which controls the initiation and progression of different tumor types. Wild-type p53 maintains cell homeostasis and genomic instability through complex pathways, and mutant p53 (Mut p53) promotes tumor occurrence and development by regulating the TME. To date, it has been wildly considered that TP53 is able to mediate tumor immune escape. Herein, we summarized the relationship between TP53 gene and tumors, discussed the mechanism of Mut p53 mediated tumor immune escape, and summarized the progress of applying p53 protein in immunotherapy. This study will provide a basic basis for further exploration of therapeutic strategies targeting p53 protein.

Seasonal wet–dry transition and denitrifying communities contributed to nitrous oxide emissions in the water-level fluctuating zone of the largest freshwater lake in China - Rui Su; Dayong Zhao; Xiaomin Zhang; Zixu Guo; Junxiang Cheng; Zhongbo Yu; Ligang Xu; Qinglong L. Wu; Jin Zeng (Journal of Hydrology, 2024)

Contrasting responses of gross N transformation to oxalic acid and glucose supplement in paddy soil - Xun Duan; Shaohong Deng; Yichao Rui; Hang Qiao; Chong Ma; Youming Zhang; Yajun Hu; Yirong Su; Jinshui Wu; Xiangbi Chen (Journal of Environmental Management, 2024)

Shifts in organic carbon protection mechanism in agricultural soils across climatic gradients - Chong Ma; Yinhang Xia; Yichao Rui; Wei Gao; Xun Duan; Hang Qiao; Xunyang He; Yajun Hu; Daoyou Huang; Jinshui Wu; Yirong Su; Georg Guggenberger; et al. (Agriculture, Ecosystems & Environment, 2024)

Photochromic ionogel with a wide temperature range and fatigue resistance for high-resolution rewritable information record - Jingyue Zhang; Mengru Guo; Yuanteng Su; Wenxia Wu; Shicheng Wang; Rui Yang; Chao Xu; Hongzong Yin; Jiaheng Xu; Xiaolin Wang (Chemical Engineering Journal, 2024)

Late Pliocene Bauhinia s.l. (Cercidoideae, Fabaceae) fossils from Tengchong, Yunnan, southwestern China - Rui Cao; Zhi-hui Song; Zhuo-er Wang; Zhao-shuai Wang; Han-shi Li; Jing-Yu Wu; Su-Ting Ding (Review of Palaeobotany and Palynology, 2024)

Metal exposure and blood lipid biomarkers in early pregnancy: A cross-sectional study - Rui Yang; Fengjiang Sun; Xiong-Fei Pan; Yingqian Su; Ping Wu; Jiaying Yuan; Yuwei Lai; An Pan; Wei Huang (Environmental Pollution, 2024)

Contrasting processes of microbial anabolism and necromass formation between upland and paddy soils across regional scales - Xun Duan; Anna Gunina; Yichao Rui; Yinhang Xia; Yajun Hu; Chong Ma; Hang Qiao; Youming Zhang; Jinshui Wu; Yirong Su; Xiangbi Chen (CATENA, 2024)

TRIM5 as a promising diagnostic biomarker of hepatocellular carcinoma: integrated analysis and experimental validation - Huanxiang Liu; Yuhong Tang; Jiahao Zhang; Gefeng Wu; Qing Peng; Chen Chen; Jun Cao; Rui Peng; Bingbing Su; Daoyuan Tu; Guoqing Jiang; Qian Wang; et al. (Functional & Integrative Genomics, 2024)

Correction to: Type I methanotrophs dominated methane oxidation and assimilation in rice paddy fields by the consequence of niche differentiation - Shengmeng Zheng; Shaohong Deng; Chong Ma; Yinhang Xia; Hang Qiao; Jun Zhao; Wei Gao; Qiang Tu; Youming Zhang; Yichao Rui; Jinshui Wu; Yirong Su; et al. (Biology and Fertility of Soils, 2024)

Type I methanotrophs dominated methane oxidation and assimilation in rice paddy fields by the consequence of niche differentiation - Shengmeng Zheng; Shaohong Deng; Chong Ma; Yinhang Xia; Hang Qiao; Jun Zhao; Wei Gao; Qiang Tu; Youming Zhang; Yichao Rui; Jinshui Wu; Yirong Su; et al. (Biology and Fertility of Soils, 2024)

Characterization of carbonaceous particles by single particle aerosol mass spectrometer in the urban area of Chengdu, China - Junke Zhang; Rui Wang; Chunying Chen; Yunfei Su; Luyao Chen; Wei Zhang; Yingwei Xi; Yangchun Yu; Ruiyan Pu; Minghui Lu; Ruohan Wu; Xuhui Shen (Environmental Science and Pollution Research, 2024)

Higher microbial C use efficiency in paddy than in adjacent upland soils: evidence from continental scale - Xun Duan; Yichao Rui; Yinhang Xia; Yajun Hu; Chong Ma; Hang Qiao; Guanjun Zeng; Yirong Su; Jinshui Wu; Xiangbi Chen (Soil and Tillage Research, 2024)

Accelerated aging of lithium-ion batteries: bridging battery aging analysis and operational lifetime prediction - Rui Li; Liying Bao; Lai Chen; Cheng Zha; Jingyang Dong; Nan Qi; Rui Tang; Yun Lu; Meng Wang; Rong Huang; Kang Yan; Yuefeng Su; et al. (Science Bulletin, 2023)

Parental exposure to environmental cadmium causes developmental defects in the rare minnow (Gobiocypris rarus) embryos: The association between ROS-mediated oxidative stress and developmental dysfunction - Liangxia Su; Huanhuan Li; Yinrui Wu; Anni Tao; Ning Qiu; Rui Wang; Liu Jun; Jianwei Wang (Journal of Environmental Chemical Engineering, 2023)

Fossil samaras of Acer L. (Sapindaceae) from the Upper Pliocene of western Yunnan, southwestern China - Zhuo-Er Wang; Rui Cao; Hong Ding; Yong-Tong Huang; Zhi-Hui Song; Su-Ting Ding; Jing-Yu Wu (Palaeobiodiversity and Palaeoenvironments, 2023)

Nano-pesticide carrier O-Carboxymethyl chitosan is indigestible in Apis cerana cerana and affects intestinal flora - Sheng-nan Li; Hao Wu; Rui-quan Hou; Jing-tong Zhou; Su-kun Lin; Kun-yu Zhao; Rui-fei Wang; Su-qing Huang; Zhi-xiang Zhang (Science of The Total Environment, 2023)

Sulfite altered permanganate effects on acetate-enriched short-chain fatty acids production during sludge anaerobic fermentation - Lijuan Wu; Rui Zhu; Xiaoxia Han; Yan Chen; Zhen Long; Hao Dong; Xiaojiang Chen; Yang Wu; Yinglong Su; Zhengyong Zhang; Jingyang Luo (Bioresource Technology, 2023)

Molecular regulation of immunity in tea plants - Lu Rui; Jia-yi Su; Tao Li; Jia-miao Sun; Guang-heng Wu (Molecular Biology Reports, 2023)

Time-frequency analysis framework for understanding non-stationary and multi-scale characteristics of sea-level dynamics - Xindan Liang; Yinyi Lin; Renguang Wu; Gang Li; Nicole Khan; Rui Liu; Hua Su; Shan Wei; Hongsheng Zhang (Frontiers in Marine Science, 2023)
Rising sea level caused by global climate change may increase extreme sea level events, flood low-lying coastal areas, change the ecological and hydrological environment of coastal areas, and bring severe challenges to the survival and development of coastal cities. Hong Kong is a typical economically and socially developed coastal area. However, in such an important coastal city, the mechanisms of local sea-level dynamics and their relationship with climate teleconnections are not well explained. In this paper, Hong Kong tide gauge data spanning 68 years was documented to study the historical sea-level dynamics. Through the analysis framework based on Wavelet Transform and Hilbert Huang Transform, non-stationary and multi-scale features in sea-level dynamics in Hong Kong are revealed. The results show that the relative sea level (RSL) in Hong Kong has experienced roughly 2.5 cycles of high-to-low sea-level transition in the past half-century. The periodic amplitude variation of tides is related to Pacific Decadal Oscillation (PDO) and El Niño-Southern Oscillation (ENSO). RSL rise and fall in eastern Hong Kong often occur in La Niña and El Niño years, respectively. The response of RSL to the PDO and ENSO displays a time lag and spatial heterogeneity in Hong Kong. Hong Kong's eastern coastal waters are more strongly affected by the Pacific climate and current systems than the west. This study dissects the non-stationary and multi-scale characteristics of relative sea-level change and helps to better understand the response of RSL to the global climate system.

Screening of microRNA and mRNA related to secondary hair follicle morphogenesis and development and functional analysis in cashmere goats - Fangzheng Shang; Yu Wang; Rong Ma; Youjun Rong; Min Wang; Zhihong Wu; Erhan Hai; Jianfeng Pan; Lili Liang; Zhiying Wang; Ruijun Wang; Rui Su; et al. (Functional & Integrative Genomics, 2022)
microRNA (miRNA) is a type of endogenous short-chain non-coding RNA with regulatory function found in eukaryotes, which is involved in the regulation of a variety of cellular and biological processes. However, the research on the development of cashmere goat secondary hair follicles is still relatively scarce. In this study, small RNA libraries and mRNA libraries of 45 days, 55 days, 65 days, and 75 days of fetal skin of cashmere goats were constructed, and the constructed libraries were sequenced using Illumina Hiseq4000, and the expression profiles of miRNA and mRNA in cashmere goat fetal skin were obtained. The differentially expressed miRNAs and mRNAs in six control groups were identified and the qRT-PCR experiment shows that the sequencing results are accurate. Sixty-six miRNAs related to secondary hair follicle development were screened, and used TargetScan and miRanda to predict 33 highly expressed miRNA target genes. At the same time, 664 mRNAs related to the development of secondary hair follicles were screened, and GO enrichment and KEGG pathway analysis were performed. It was found that some miRNA target genes were consistent with the screening results of mRNAs related to secondary hair follicle development and were enriched in Notch signaling pathway, TGF-β signaling pathway. Therefore, miR-145-5p-DLL4, miR-27b-3p-DLL4, miR-30e-5p-DLL4, miR-193b-3p-TGF-β1, miR-181b-5p-NOTCH2, and miR-103-3p-NOTCH2 regulatory network related to the development of secondary hair follicles were constructed and the results of dual-luciferase reporter gene assay indicated that there is a targeted relationship between chi-miR-30e-5p and DLL4, which will provide a basis for molecular mechanism of miRNA-mRNA in the development of the hair follicles in cashmere goats.

Transcriptomic Analysis of Circulating Neutrophils in Sheep with Mineral Element Imbalance - Di Wang; Ming Ji; Qijun Zhou; Chengyuan Su; Shuai Lian; Jianfa Wang; Jiasan Zheng; Rui Wu (Biological Trace Element Research, 2022)

Leaf and canopy photosynthesis of four desert plants: considering different photosynthetic organs - Zijuan Zhou; Peixi Su; Xiukun Wu; Haina Zhang; Rui Shi; Jianping Yang (Photosynthesis Research, 2022)

Physiological Responses of Ribosomal Protein S12 K43 Mutants of Corynebacterium glutamicum - Guihong Zhao; Rui Su; Meng Yuan; Hongkun Ma; Taidong Bo; Hao Jiang; Chen Wu; Yanjun Li (Current Microbiology, 2022)

Rhizosphere-associated nosZII microbial community of Phragmites australis and its influence on nitrous oxide emissions in two different regions - Rui Su; Rui Huang; Jin Zeng; Dayong Zhao; Rujia He; Zhongbo Yu; Qinglong L. Wu (Journal of Soils and Sediments, 2021)

Contrasting pathways of carbon sequestration in paddy and upland soils - Xiangbi Chen; Yajun Hu; Yinhang Xia; Shengmeng Zheng; Chong Ma; Yichao Rui; Hongbo He; Daoyou Huang; Zhenhua Zhang; Tida Ge; Jinshui Wu; Georg Guggenberger; et al. (Global Change Biology, 2021)
Paddy soils make up the largest anthropogenic wetlands on earth, and are characterized by a prominent potential for organic carbon (C) sequestration. By quantifying the plant‐ and microbial‐derived C in soils across four climate zones, we identified that organic C accrual is achieved via contrasting pathways in paddy and upland soils. Paddies are 39%–127% more efficient in soil organic C (SOC) sequestration than their adjacent upland counterparts, with greater differences in warmer than cooler climates. Upland soils are more replenished by microbial‐derived C, whereas paddy soils are enriched with a greater proportion of plant‐derived C, because of the retarded microbial decomposition under anaerobic conditions induced by the flooding of paddies. Under both land‐use types, the maximal contribution of plant residues to SOC is at intermediate mean annual temperature (15–20°C), neutral soil (pH~7.3), and low clay/sand ratio. By contrast, high temperature (~24°C), low soil pH (~5), and large clay/sand ratio are favorable for strengthening the contribution of microbial necromass. The greater contribution of microbial necromass to SOC in waterlogged paddies in warmer climates is likely due to the fast anabolism from bacteria, whereas fungi are unlikely to be involved as they are aerobic. In the scenario of land‐use conversion from paddy to upland, a total of 504 Tg C may be lost as CO 2 from paddy soils (0–15 cm) solely in eastern China, with 90% released from the less protected plant‐derived C. Hence, preserving paddy systems and other anthropogenic wetlands and increasing their C storage through sustainable management are critical for maintaining global soil C stock and mitigating climate change.

Correction to: Strong phosphorus (P)-zinc (Zn) interactions in a calcareous soil-alfalfa system suggest that rational P fertilization should be considered for Zn biofortification on Zn-deficient soils and phytoremediation of Zn-contaminated soils - Honghua He; Miaomiao Wu; Rui Su; Zekun Zhang; Chao Chang; Qi Peng; Zhigang Dong; Jiayin Pang; Hans Lambers (Plant and Soil, 2021)

Strong phosphorus (P)-zinc (Zn) interactions in a calcareous soil-alfalfa system suggest that rational P fertilization should be considered for Zn biofortification on Zn-deficient soils and phytoremediation of Zn-contaminated soils - Honghua He; Miaomiao Wu; Rui Su; Zekun Zhang; Chao Chang; Qi Peng; Zhigang Dong; Jiayin Pang; Hans Lambers (Plant and Soil, 2021)

The geological characteristics of the large- and medium-sized gas fields in the South China Sea - Gongcheng Zhang; Dongdong Wang; Lei Lan; Shixiang Liu; Long Su; Long Wang; Wu Tang; Jia Guo; Rui Sun (Acta Oceanologica Sinica, 2021)

Erratum to: Transmission risk of patients with COVID-19 meeting discharge criteria should be interpreted with caution - Jun-wei Su; Wen-rui Wu; Guan-jing Lang; Hong Zhao; Ji-fang Sheng (Journal of Zhejiang University-SCIENCE B, 2020)

Transmission risk of patients with COVID-19 meeting discharge criteria should be interpreted with caution - Jun-wei Su; Wen-rui Wu; Guan-jing Lang; Hong Zhao; Ji-fang Sheng (Journal of Zhejiang University-SCIENCE B, 2020)

Release of tartrate as a major carboxylate by alfalfa (Medicago sativa L.) under phosphorus deficiency and the effect of soil nitrogen supply - Honghua He; Miaomiao Wu; Lei Guo; Chenbin Fan; Zekun Zhang; Rui Su; Qi Peng; Jiayin Pang; Hans Lambers (Plant and Soil, 2020)

Overexpression of BcbZIP134 negatively regulates the biosynthesis of saikosaponins - Jiao Xu; Su-Rui Wu; Yan-Hong Xu; Zhan-Yu Ge; Chun Sui; Jian-He Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Enemy-free space is important in driving the host expansion of a generalist herbivore to an inferior exotic plant in a wetland of Yangtze Estuary - Jing Zhang; Rui-Ting Ju; Hui Pan; Su-Feng Pan; Jie Wu (Biological Invasions, 2019)

Agmatine Prevents Adaptation of the Hippocampal Glutamate System in Chronic Morphine-Treated Rats - Xiao-Fei Wang; Tai-Yun Zhao; Rui-Bin Su; Ning Wu; Jin Li (Neuroscience Bulletin, 2016)

Oral administration of Schisandra chinensis extract suppresses Dnmt1 expression in Kunming mice ovaries - Feng-Rui Wu; Deng-kun Li; Mi-mi Su; Yong Liu; Biao Ding; Rong Wang; Wen-yong Li (Genes & Genomics, 2016)

Ethanol Increases Mechanical Pain Sensitivity in Rats via Activation of GABAA Receptors in Medial Prefrontal Cortex - Kai-Wen Geng; Ting He; Rui-Rui Wang; Chun-Li Li; Wen-Jun Luo; Fang-Fang Wu; Yan Wang; Zhen Li; Yun-Fei Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Impact of temperature variation between adjacent days on childhood hand, foot and mouth disease during April and July in urban and rural Hefei, China - Jian Cheng; Rui Zhu; Zhiwei Xu; Jinju Wu; Xu Wang; Kesheng Li; Liying Wen; Huihui Yang; Hong Su (International Journal of Biometeorology, 2016)

Canyon-related undulation structures in the Shenhu area, northern South China Sea - Shaohua Qiao; Ming Su; Zenggui Kuang; Rui Yang; Jinqiang Liang; Nengyou Wu (Marine Geophysical Research, 2015)

Migration of methane associated with gas hydrates of the Shenhu Area, northern slope of South China Sea - Rui Yang; Ming Su; Shaohua Qiao; Xiaorong Cong; Zheng Su; Jinqiang Liang; Nengyou Wu (Marine Geophysical Research, 2015)

Cloning and analysis of β-amyrin synthase gene in Bupleurum chinense - Ke Gao; Su-rui Wu; Ling Wang; Yan-hong Xu; Jian-he Wei; Chun Sui (Genes & Genomics, 2015)

Monitoring and modeling the effects of groundwater flow on arsenic transport in Datong Basin - Qian Yu; Yanxin Wang; Rui Ma; Chunli Su; Ya Wu; Junxia Li (Journal of Earth Science, 2014)

Spatial analysis of phytoplankton patterns in relation to environmental factors across the southern Taihu basin, China - Rui Xiao; Shiliang Su; Anas Ghadouani; Jiaping Wu (Stochastic Environmental Research and Risk Assessment, 2013)

Multi-scale spatial determinants of dissolved oxygen and nutrients in Qiantang River, China - Shiliang Su; Rui Xiao; Xiangyang Xu; Zhonghao Zhang; Xiaoya Mi; Jiaping Wu (Regional Environmental Change, 2013)

Geospatial assessment of agroecosystem health: development of an integrated index based on catastrophe theory - Shiliang Su; Zhonghao Zhang; Rui Xiao; Zhenlan Jiang; Tao Chen; Limin Zhang; Jiaping Wu (Stochastic Environmental Research and Risk Assessment, 2012)

Assessing land ecological security in Shanghai (China) based on catastrophe theory - Shiliang Su; Dan Li; Xiang Yu; Zhonghao Zhang; Qi Zhang; Rui Xiao; Junjun Zhi; Jiaping Wu (Stochastic Environmental Research and Risk Assessment, 2011)

Geology and geochemistry of Carlin-type gold deposits in China - Hu Rui-Zhong; Su Wen-Chao; Bi Xian-Wu; Tu Guang-Zhi; Albert Hofstra (Mineralium Deposita, 2002)